Training, Human Capital, and Gender Gaps in Entrepreneurial Performance - Zuzana Brixiova; Thierry Kangoye; Mona Said (Institute of Labor Economics (IZA), 2019)
In the aftermath of the global financial crisis, policymakers have been increasingly striving to support female entrepreneurship as a possible growth driver. This paper contributes to reconciling mixed findings in the literature on the effectiveness of entrepreneurial training with an analysis that links training and human capital, including tertiary education and non-cognitive skills, with gender gaps in entrepreneurial performance in Africa. We have found that while financial literacy training directly benefits men, it does not raise the sales level of women entrepreneurs. Instead, tertiary education has a direct positive link with the performance of women. Consistent with our theoretical model where different skills are complements, tertiary education can act as a channel that makes training effective. Regarding non-cognitive skills, evidence shows that women entrepreneurs who are tenacious achieve stronger sales performance. Our results underscore the importance of incorporating tertiary education and entrepreneurial training programs focused on a balanced set of skills, including non-cognitive skills, among policies for women entrepreneurs.
Keywords: L53; O12; J4; 330; non-cognitive skills; training; female entrepreneurship; tertiary education